Cross Media dan Remediasi Soundwork Suara Surabaya FM 100 dan PRFM - Yudhapramesti, Pandan (Jurnal ILMU KOMUNIKASI, 2023)
Broadcast radio faces challenges in maintaining its existence, particularly in the internet era. Audiences now have more media access choices, leading to decreased loyalty to a single medium. This research explores the strategy of expanding the reach of broadcast radio through cross-media initiatives in the new internet-based medium. It also examines the process of soundwork remediation within the internet medium, focusing on Suara Surabaya FM 100 and PRFM radio. The new context of remediation enables the establishment of social connections between the audience and radio, as well as connectivity among the audience mediated by radio across different outlets.